Leishmania Heat Shock Proteins as Effectors of Immune Evasion and Virulence - Bartsch, Katharina; Eick, Julia; Zirpel, Henner; Clos, Joachim (Current Immunology Reviews (Discontinued), 2017)
Historically, heat shock proteins were seen foremost as playing roles in stress protection and short term adaption to changing environmental parameters. This view is now superseded by findings that implicate HSPs in various aspects of cell regulation, protein maturation and modulation, immune response and immune modulation. Likewise in parasitic protozoa, the old view of HSPs as protecting the pathogens against the harsh conditions inside mammalian hosts has given way to a far broader picture in which parasite HSPs play decisive regulatory roles in primitive protozoa, regulating cell cycle, life cycle, morphology and protein trafficking and thus affecting viability, infectivity, virulence and host immune responses. In this review, we discuss the impact of Leishmania heat shock proteins on viability and survival inside mammalian host organisms.
Keywords: Parasite